2021
DOI: 10.1002/cb.1937
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the boycott behavior: A conceptual model proposal and validation

Abstract: This study proposes a conceptual model with the capacity to substantially explain the boycott behavior. As a first step for the validation of the proposed model, an empirical study has been carried out, focusing on the boycott promoted towards the territory of Catalonia (Spain). Following the postulates of the theory of reasoned action, the effect that the intention to participate in the boycott will have on effective behavior is considered, but social influence, the importance given to brands and the perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Fourth, in alignment with the study results, economic animosity significantly positively influences boycott visit intention, so H3 has been accepted. This research finding is in line with previous explorations (Rose et al, 2009 ; Palacios-Florencio et al, 2021 ), in which it has been revealed that animosity generates a significant impact on boycott intention, namely, animosity is a motivating factor for boycott intention. Moreover, it has been demonstrated that consumer animosity significantly positively affects Korean consumers' intention of boycotting Japanese food and clothes together with travel to Japan (Lee and Chon, 2022 ), which is also a supporting point for the positive bearings of animosity on boycott intention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Fourth, in alignment with the study results, economic animosity significantly positively influences boycott visit intention, so H3 has been accepted. This research finding is in line with previous explorations (Rose et al, 2009 ; Palacios-Florencio et al, 2021 ), in which it has been revealed that animosity generates a significant impact on boycott intention, namely, animosity is a motivating factor for boycott intention. Moreover, it has been demonstrated that consumer animosity significantly positively affects Korean consumers' intention of boycotting Japanese food and clothes together with travel to Japan (Lee and Chon, 2022 ), which is also a supporting point for the positive bearings of animosity on boycott intention.…”
Section: Discussionsupporting
confidence: 92%
“…Fourth, in alignment with the study results, economic animosity significantly positively influences boycott visit intention, so H3 has been accepted. This research finding is in line with previous explorations (Rose et al, 2009;Palacios-Florencio et al, 2021), in which it has been revealed that animosity generates a significant impact on boycott intention, namely, animosity is a motivating factor for boycott intention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the one hand, intrinsic motivations are likely to activate boycotting behaviors because they are personally rewarding and reflect fundamental concerns for other people or the environment. In particular, Ethical Idealism (Palacios-Florencio et al 2021) captures consumers’ concerns about the possible adverse effects of their personal conduct on others. On the other hand, extrinsic motivations are likely to activate boycotting behaviors insofar as consumers believe that boycotting will stimulate positive evaluations from their social referents.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Likewise, academic research suggests that Gen Zers are increasingly paying attention to social and environmental issues in their consumption behavior, forcing brands to think about the causes they are willing to support. This generation is active in fighting for systemic and transformative societal change; one path to accomplish this is to speak out and stand up for their values when faced with the egregious behaviors of companies, brands, or groups (Klein, Smith, and John 2004; Luttrell and McGrath 2021; Palacio-Florencio et al 2021; Ziesemer, Hüttel, and Balderjahn 2021). Young adult consumers hold particularly sophisticated skills and critical attitudes toward the marketplace and are quick to use boycotts to challenge the status quo (Harris, Wyn, and Younes 2010; Palan, Gentina, and Muratore 2010; Ziesemer, Hüttel, and Balderjahn 2021).…”
mentioning
confidence: 99%